Pengaruh Economic Value Added (EVA) Momentum Terhadap Shareholder Value Dengan Corporate Governance Sebagai Variable Pemoderasi (Studi Pada Perusahaan Yang Terdaftar Dalam Indeks LQ 45 Bursa Efek Indonesia Periode 2013-2015) - Darmawangsa, Ramadhan (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research is conducted to obtain empirical evidence that (1) there is an influence of EVA Momentum on shareholder value, (2) the influence of corporate governance mechanism as a moderating variable of EVA Momentum and shareholder value relationship. The sample in this research consisted of 21 companies that listed continuously included in the LQ45 list and publish in the Indonesia Stock Exchange (IDX) from 2013 to 2015.. A regression analysis is use to test the hypothesis. Hypothetical test results show that EVA Momentum have a positive influence on shareholder value. Besides that, test results also show that corporate governance is a moderating variable to the influence of EVA Momentum on shareholder value. In other word, we can say that corporate governance practices can strengthen the influence of EVA Momentum on shareholder value. Keywords : EVA Momentum, Shareholer Value, Corporate Governance. Moderating Variable